The transforming growth factor beta ligand TIG-2 modulates the function of neuromuscular junction and muscle energy metabolism in Caenorhabditis elegans - Cheng, Xinran; Yan, Zhenzhen; Su, Zexiong; Liu, Jie (Frontiers in Molecular Neuroscience, 2022)
Deciphering the physiological function of TGF-β (the Transforming Growth Factor beta) family ligands is import for understanding the role of TGF-β in animals’ development and ageing. Here, we investigate the function of TIG-2, one of the ligands in C. elegans TGF-β family, in animals’ behavioral modulation. Our results show that a loss-of-function mutation in tig-2 gene result in slower locomotion speed in the early adulthood and an increased density of cholinergic synapses, but a decreased neurotransmitter release at neuromuscular junctions (NMJs). Further tissue-specific rescue results reveal that neuronal and intestinal TIG-2 are essential for the formation of cholinergic synapses at NMJs. Interestingly, tig-2(ok3416) mutant is characterized with reduced muscle mitochondria content and ATP production, although the function of muscle acetylcholine receptors and the morphology muscle fibers in the mutant are comparable to that in wild-type animals. Our result suggests that TIG-2 from different neuron and intestine regulates worm locomotion by modulating synaptogenesis and neurotransmission at NMJs, as well as energy metabolism in postsynaptic muscle cells.